A segunda tela na tv digital brasileira: um estudo dos processos midiáticos interativos - Bernardini, Gleice [UNESP] (2015)
The research aims to analyze the possibilities of using the interactivity in the Second Screen tool. The Brazilian Digital TV brought with in the possibility of the viewer interact with the television content through tablets, mobile and other technological devices, such as in apps, content platforms to browse or in social networks. Thus, many authors have named the new experiences as Second Screen and Social TV. But, many times because they are aggregated with a digital televisional content, they are mistaken as a single platform. Through a 'transmetodologíca' research with a documentary literature, we try to discuss issues in order to provide a study of deepening as the base for a possible definition of concepts and to establish the differences and similarities between the two technologies. To this end, and exploratory field study will be used in order to exemplify the current reality. What we observe is that there is a necessity to publish these technologies and how they work in order to extend knowledge or the Second Screen tool. We aim, even though new questions, to disseminate and build aggregate knowledge about the themes and their use in the standard of Brazilian Digital TV, to improve understanding of the population about these innovations